Facial image protection with visual cryptography and random least significant bit (LSB) steganography - Karo Karo, Panser; Simarmata , Simon; Faizah, Novianti Madhona; Fabrianto, Luky (Jurnal Mandiri IT, 2025)
The confidentiality of sensitive data—such as personal information of individuals who may pose security threats to client assets—must be strictly maintained. This data includes personal details such as name, ID number, address, date of birth, occupation, and photographs (images). The data protection process involves combining textual data (ID number, name, date of birth) with a photo into a single image, which is then processed using visual cryptography. The visual cryptography technique applied is the (k, n) scheme with a 2-out-of-k configuration. To enhance data security and confidentiality through dual-layer protection, the output from the visual cryptography process is further secured using steganography with the random LSB (Least Significant Bit) method, applied to one of the shares obtained from the previous step. The best result achieved during testing was a PSNR of 71.9977 and an MSE of 0.0041. It is expected that the combination of visual cryptography and steganography methods will significantly enhance the security of data storage to protecting it from unauthorized access.